2021
DOI: 10.1519/jsc.0000000000003135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interlimb Asymmetries on Acceleration and Change of Direction Speed: A Between-Sport Comparison of Professional Soccer and Cricket Athletes

Abstract: The first aim of the present study was to quantify and compare asymmetries among professional soccer and cricket athletes. The second aim was to examine the association between asymmetries and performance within both groups. Professional soccer (n = 18) and cricket (n = 23) athletes performed single leg countermovement jumps (SLCMJ), single leg drop jumps (SLDJ), a 10 m sprint and 505 change of direction speed (CODS) tests. Inter-limb asymmetries were calculated as a standard percentage difference, Mann-Whitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 43 publications
9
58
1
Order By: Relevance
“…For example, Lockie et al (2014) reported ILA scores of 10.4, 5.1 and 3.3% for the CMJ UL , lateral and broad jump, respectively, which confirm the variability between unilateral jump tasks often reported in previous studies [5,12,13,15]. For CoD speed, it has been suggested that total time may not be overly sensitive at detecting existing ILAs [8,13,16], with mean values >3% rarely being reported. Thus, given the inherent differences in ILA values which may arise from different tests, it is advised that a battery of tests is used, rather than a single test, to provide a more meaningful picture of the task-specific nature of ILA.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…For example, Lockie et al (2014) reported ILA scores of 10.4, 5.1 and 3.3% for the CMJ UL , lateral and broad jump, respectively, which confirm the variability between unilateral jump tasks often reported in previous studies [5,12,13,15]. For CoD speed, it has been suggested that total time may not be overly sensitive at detecting existing ILAs [8,13,16], with mean values >3% rarely being reported. Thus, given the inherent differences in ILA values which may arise from different tests, it is advised that a battery of tests is used, rather than a single test, to provide a more meaningful picture of the task-specific nature of ILA.…”
Section: Introductionsupporting
confidence: 77%
“…Loud verbal encouragement was consistently provided to ensure maximum effort. For each task (90 and 180 • turn) and side (preferred, non-preferred), the main outcome measure was the total time (s) [8].…”
Section: And 180 • Change Of Direction Speedmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-reactive agility involves an active change of direction speed (CODS). Consequently, the term “pre-planned agility” is regularly used for CODS, while RAG is often referred to as “non-planned agility” [13,18,19].…”
Section: Introductionmentioning
confidence: 99%